If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying j + 2 = 14 Reorder the terms: 2 + j = 14 Solving 2 + j = 14 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + j = 14 + -2 Combine like terms: 2 + -2 = 0 0 + j = 14 + -2 j = 14 + -2 Combine like terms: 14 + -2 = 12 j = 12 Simplifying j = 12
| 15c=5 | | 2x+105=6x | | N+2n=57 | | -X+3(3)=12 | | -5x+10=-14-x | | 356b+56=-832 | | -17s+13s-8=-12 | | 2y-2y+y=17 | | 3x+1.5=6 | | 54=m(m-3) | | 8j(4k)= | | 15(x)=6+14(x) | | 2(x+2)=-6 | | -832=56b+356 | | 224=(W-8)+W+(W-8)+W | | -2(n-7)=-6 | | 16m-7m=18 | | 128=(W-8)+W+(W-8)+W | | 12q-7q=20 | | 3x^2+10=110+x^2 | | 7x+5=3x+17-3x | | ((cos^2)(x))+2cosx+1=0 | | -8+5b+7=b+5+6 | | 8*1-18= | | -18m+6m-2m=14 | | -2(3n-5)-(3-4n)=-3 | | -X+2(1)=6 | | -8x=10-(-14) | | 7h-(-8h)-16h=17 | | (15a+3b)+(a+3b-4)= | | 2=1k+-32 | | 6x-3=4x+3+2x |